2012
DOI: 10.3406/revec.2012.1621
|View full text |Cite
|
Sign up to set email alerts
|

A precipitous decline of the Algerian Newt Pleurodeles poireti Gervais, 1835 and other changes in the status of amphibians ofNumidia, North-Eastern Algeria

Abstract: The worldwide erosion of biological diversity has not spared amphibians which are amongst the most affected taxa with numerous extinct or near-extinct species. Our knowledge of the status and ecology of amphibians of Algeria is still limited whereas local natural habitats are fast disappearing under a strong anthropogenic pressure. Eighty two localities were sampled between 1996 and 2010, to survey the amphibian community within Numidia, North-Eastern Algeria. Nine species, three Urodeles (Pleurodeles poireti,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although numerous recent studies clearly indicated that newts are in an obvious decline (e.g., Denoël, 2012;Samraoi et al, 2012;Arntzen et al, 2017;von Bülow and Kupfer, 2019;Falaschi et al, 2022), our results indicated that in JGNP both species register important increases in their populations. Thus, in the habitat from Comandă, T. cristatus population increased by 1.80 times in 10 years, and L. vulgaris population increased by 2.58 in the same time interval, compared with the previous data (Dobre et al, 2009).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Although numerous recent studies clearly indicated that newts are in an obvious decline (e.g., Denoël, 2012;Samraoi et al, 2012;Arntzen et al, 2017;von Bülow and Kupfer, 2019;Falaschi et al, 2022), our results indicated that in JGNP both species register important increases in their populations. Thus, in the habitat from Comandă, T. cristatus population increased by 1.80 times in 10 years, and L. vulgaris population increased by 2.58 in the same time interval, compared with the previous data (Dobre et al, 2009).…”
Section: Discussioncontrasting
confidence: 79%
“…Thus, in northern Italy, in the case of two newt species, the population reduction was between 57% and 63% and was caused in the first place by invasive fish and crayfish (Falaschi et al, 2022). Besides these, there are other studies that document reductions in newt populations (e.g., Griffiths et al, 2010;Samraoi et al, 2012;Arntzen et al, 2017;Sinsch et al, 2018;von Bülow and Kupfer, 2019). Nevertheless, newts decline seems to be more documented in Western Europe (see Denoël, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the area is rich in micro‐endemics such as the Edough ribbed newt, Pleurodeles poireti (Gervais, 1835), the Algerian ribbed newt, Pleurodeles nebulosus (Guichenot, 1850), and the Endangered minnow Pseudophoxinus punicus (Pellegrin, 1920) (García et al, 2010; Samraoui et al, 2012). Similarly, a suite of micro‐endemic stoneflies (Yasri‐Cheboubi, Vinçon & Lounaci, 2013; Yasri‐Cheboubi, Vinçon & Lounaci, 2016) and mayflies (Samraoui et al, 2021; Kaltenbach et al, 2022) are present in the area.…”
Section: Discussionmentioning
confidence: 99%